IMPROVING CITRONELLA OIL PROCESSING MARKET ACCESS FOR SMALL AND MEDIUM ENTERPRISES TO OVERCOME - Diana Chalil; Riantri Barus (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Citronella oil production has been developed by the Regional Government of the South Tapanuli District through the Forest Management Unit (KPH), the Agriculture Office and the Industry Office. For KPH, this program serves to gradually replace oil palm smallholdings in forest areas. For the Agriculture and Industry Offices, this program is intended to increase farmer income, especially during the Covid19 Pandemic. However, businesses have faltered as citronella oil prices dropped dramatically. Many farmers cannot survive and temporarily close their business. This is mainly caused by the limited market access of farmers due to an inadequate business scale and production quality. To overcome such a condition, farmers need to have a strong smallholder institution with a sufficient economic scale, as well as good coordination among stakeholders. This activity was carried out for 3 months through online and offline meetings. Farmers were introduced to both export and local market accesses. However, to utilize these opportunities farmers need to have a strong and adequate farmer institution. Through the Forum Group Discussion, progressive farmers and processors were gathered with farmers from 3 other sub districts, as well as other stakeholders related to the improvement of market access. The results showed that farmers and other stakeholders agreed to jointly support the development of the citronella oil industry in South Tapanuli. The FGD ended with the commitment of farmers and all stakeholders to form a South Tapanuli Citronella Oil multi-stakeholders Forum to improve the ability to deal with market fluctuations in the future.